Effects of rare-earth oxide doping on the thermal radiation performance of HfO2 coating. Issue 10 (July 2019) - Liu, Fusheng; Cheng, Xudong; Mao, Jiawei; Li, Qingyu; Zeng, Xian
Abstract: In this study, the REO-HfO2 (REO = Tb4 O7, Gd2 O3 and Sm2 O3 ) coatings and pure HfO2 coatings were prepared by atmospheric plasma spraying. The chemical compositions, morphologies, infrared radiation performance and thermal resistances of the coatings were systematically investigated. The experimental results showed that the Tb4 O7 -HfO2, Gd2 O3 -HfO2, Sm2 O3 -HfO2 and pure HfO2 coatings had infrared emissivity values of 0.863, 0.852, 0.854 and 0.621, respectively, at room temperature. Based on the phase analysis, the higher infrared emissivity of the REO-HfO2 coatings could be attributed to the fact that the newly formed RE2 Hf2 O7 (RE = Tb, Gd and Sm) phase, which had a defective fluorite-type structure, and the RE 3+ ions enhanced the lattice absorption and electron absorption. Additionally, the Tb4 O7 -HfO2 coating exhibited a relatively higher infrared emissivity than those of the Gd2 O3 -HfO2 and Sm2 O3 -HfO2 coating over the wavelength range of 1–15 μm, which was due to the relatively higher vibrational frequency of the TbO bond in RE2 Hf2 O7 (RE = Tb, Gd and Sm) and the transformation of Tb 3+ into Tb 4+ in the Tb4 O7 -HfO2 system. In addition, the REO-HfO2 ceramic coatings exhibited excellent thermal resistance, which could withstand high-temperature treatment at 1600 °C for at least 50 h without undergoing a phase change and exfoliation, and the infrared emissivity at different temperatures hardly changed after thermal treatment.